A process evaluation in the pilot implementation of Alternative Learning System Senior High School in the School Division of Aurora - Noveras, Carlo V. (Aurora ASCOT, 2023)
To follow with curriculum changes in formal school, ALS also include SHS in their program to cater out-of-school children in special cases, youth, and adults who wanted to graduate SHS. However, because of its being new, implementation is a shot on the dark. With this mind, this study conducted a process evaluation in the pilot implementation of Alternative Learning System Senior High School in the Schools Division of Aurora. A duly validated semi-structured interview guide was the main instrument in data gathering and being analyzed using simple frequency count and thematic analysis model suggested by Clarke and Braun (2006). Results indicate that ALS SHS Program in the division seems to be on the right track as the number of enrolees increased to 193.57% on just its second year of implementation. The learning resources were adapted to the existing modules from formal school, localized and contextualized to make it suited to the ALS Senior High School Competencies. The strong linkages with the different partners in the implementation was also showed in the result of the interview. Blended learning and flexible learning are being offered as a learning delivery modality. As a result, those who were not able to study in formal school may have a chance to finish Basic Education. However, different challenges such as low graduation rate, lack of full-time ALS-SHS teachers, insufficient classroom facility for A&E learning session were revealed. Therefore, it is highly recommended that ALS-SHS must be expanded throughout the province to cater more students offering all the SHS specialization in TVL and Academic tracks to make the students choose courses based on their preferences, partnerships and linkages should be sustained and augmented, hire additional teachers, and there should be a standardized test nationwide assessing the learning of the students to ensure comparison among implementing schools with regard to student achievement, accountability for teachers and serve as the basis for data-driven instruction.
Master of Arts in Education Major in Educational Management
Keywords: Alternative Learning System